2015
DOI: 10.1161/strokeaha.115.009371
|View full text |Cite
|
Sign up to set email alerts
|

Duration of Diabetes Mellitus and Risk of Thromboembolism and Bleeding in Atrial Fibrillation

Abstract: Background and Purpose-Guidelines advocate anticoagulant treatment to all patients with atrial fibrillation and concomitant diabetes mellitus. The potential refinement to thromboembolic risk stratification that may spring from subdividing diabetes mellitus is unexplored. The purpose was to investigate duration of diabetes mellitus as a predictor of thromboembolism and anticoagulant-related bleeding in patients with atrial fibrillation. Methods-Using nationwide Danish registries, we identified all patients disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
3
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(55 citation statements)
references
References 40 publications
3
47
3
2
Order By: Relevance
“…In the study of Overvad et al, during 4 years of diabetes in patients on OAC, the incidence rate of bleeding was 6.8, whereas in the present cohort of patients there were no episodes of severe bleeding. Overvad et al also found that indication of a lower bleeding risk with a longer duration of DM. In a study of patients with type 1 DM, the duration of DM was found to be a risk predictor for ischemic stroke, but not hemorrhagic stroke .…”
Section: Discussioncontrasting
confidence: 62%
See 2 more Smart Citations
“…In the study of Overvad et al, during 4 years of diabetes in patients on OAC, the incidence rate of bleeding was 6.8, whereas in the present cohort of patients there were no episodes of severe bleeding. Overvad et al also found that indication of a lower bleeding risk with a longer duration of DM. In a study of patients with type 1 DM, the duration of DM was found to be a risk predictor for ischemic stroke, but not hemorrhagic stroke .…”
Section: Discussioncontrasting
confidence: 62%
“…However, the observed bleeding rates in patients with versus without diabetes are inconsistent . In the study of Overvad et al, during 4 years of diabetes in patients on OAC, the incidence rate of bleeding was 6.8, whereas in the present cohort of patients there were no episodes of severe bleeding. Overvad et al also found that indication of a lower bleeding risk with a longer duration of DM.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…Although T2DM has been associated with increased incidence of AF in the general population and with a higher risk of stroke and thromboembolism among patients with AF, a limited number of studies have investigated the prevalence and prognostic impact of T2DM on non‐thromboembolic outcomes in individuals with AF. The reported prevalence of T2DM in contemporary observational studies and clinical trials of AF patients has shown a broad variation (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Cukrzyca jest czynnikiem ryzyka udaru mózgu i innych powikłań AF [284]. U pacjentów z AF dłuższy czas trwania cukrzycy wydaje się związany z większym ryzykiem powikłań zakrzepowo-zatorowych, natomiast nie zwiększa ryzyka krwawień związanych z OAC [285]. Niestety, intensywna kontrola glikemii nie wpływa na częstość występowania nowego AF [284], chociaż wydaje się, że leczenie metforminą wiąże się ze zmniejszeniem długoterminowego ryzyka AF u chorych na cukrzycę [286], a być może nawet z mniejszym ryzykiem udaru mózgu w długoterminowej obserwacji [13].…”
Section: Cukrzycaunclassified